Altered viscerotopic cortical innervation in patients with irritable bowel syndrome. Issue 8 (7th May 2015) - Irimia, A.; Labus, J. S.; Torgerson, C. M.; Van Horn, J. D.; Mayer, E. A.
Abstract Background Studies have demonstrated the existence of regional gray matter and white matter (WM) alterations in the brains of patients with irritable bowel syndrome (IBS), but the extent to which altered anatomical connectivity between brain regions is altered in IBS remains incompletely understood. Methods In this study, magnetic resonance imaging (MRI) and diffusion tensor imaging (DTI) were used to identify significant brain connectivity differences between IBS patients and healthy control (HC) subjects. Based on MRI and DTI volumes acquired from 66 IBS patients and 23 HC subjects, multivariate regression was used to investigate whether subject age, sex, cortical thickness, or the mean fractional anisotropy (FA) of WM connections innervating each location on the cortex could predict IBS diagnosis. Key Results HC and IBS subjects were found to differ significantly within both left and right viscerotopic portions of the primary somatosensory cortex (S1), with the mean FA of WM bundles innervating S1 being the predictor variable responsible for these significant differences. Conclusions & Inferences These preliminary findings illustrate how a chronic visceral pain syndrome and brain structure are related in the cohort examined, and because of their indication that IBS diagnosis is associated with anatomic neuropathology of potential neurological relevance in this patient sample.